X-Ray Fluorescence Determination of Trace Elements in Vitamin-Mineral Complexes and Medicinal Herbs Using Chemically Modified Polyurethane Foam Sorbents - Alexander Chaplenko; Oksana Monogarova; Kirill Oskolok (College of Pharmacy University of Baghdad, 2018)
In this paper we proposed the method of X-ray fluorescence (XRF) determination of some essential trace elements in medicinal herbs and vitamin-mineral complexes at the level of 100-101 mg/ml. To increase sensitivity and selectivity of the determination we simple and effective approach based on the extraction of metal ions from aqueous solutions with chemically modified polyurethane foam sorbents followed by direct XRF analysis. The conditions of sorption preconcentration of Co(II), Ni(II) and Zn(II) ions with modified sorbents were optimized. The proposed approach is used for the determination of trace elements in several kinds of medicinal herbs (coltsfoot leaves, nettle leaves and yarrow herb) and vitamin-mineral complexes («Alfavit», «Vitrum» and «Multi-tabs»).